A hybrid wave-mode formulation for the vibro-acoustic analysis of 2D periodic structures. (17th February 2016) - Droz, C.; Zhou, C.; Ichchou, M.N.; Lainé, J.-P.
Abstract: In the framework of vibrational analysis of 2D periodic waveguides, Floquet–Bloch theorem is widely applied for the determination of wave dispersion characteristics. In this context, the Wave Finite Element Method (WFEM) combines Periodic Structure Theory (PST) with standard FE packages, enabling wave dispersion analysis of waveguides involving structurally realistic unit-cells. For such applications, the computational efficiency of the WFEM depends on the choice of the formulation and can lead to numerical issues, worsen by extensive computational cost. This paper presents a coupled wave-mode approach for the determination of wave dispersion characteristics in structurally advanced periodic structures. It combines two scales of model order reduction. At the unit-cell׳s scale, Component Mode Synthesis (CMS) provides the displacement field associated with local resonances of the periodic structure, while the free wave propagation is considered using a spectral problem projection on a reduced set of shape functions associated with propagating waves, thus providing considerable reduction of the computational cost. An application is provided for a bi-directionally stiffened panel and the influence of reduction parameters is discussed, as well as the robustness of the numerical results.